2014
DOI: 10.1089/neu.2013.3143
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic and Vascular Remodeling in the Injured Adult Rat Spinal Cord after Chondroitinase ABC Treatment

Abstract: Upregulation of extracellular chondroitin sulfate proteoglycans (CSPG) is a primary cause for the failure of axons to regenerate after spinal cord injury (SCI), and the beneficial effect of their degradation by chondroitinase ABC (ChABC) is widely documented. Little is known, however, about the effect of ChABC treatment on astrogliosis and revascularization, two important factors influencing axon regrowth. This was investigated in the present study. Immediately after a spinal cord hemisection at thoracic level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 88 publications
(130 reference statements)
3
38
0
Order By: Relevance
“…tPA deletion attenuated neurite outgrowth and sensory/motor functional recovery due to ChABC treatment and coadministration of ChABC and plasmin reversed the effects of tPA deficiency. ChABC treatment induced an extended period of astrocyte remodeling (up to 4 weeks) and a favored orientation of astrocytic processes directed toward injury area, which might become guidance bridges for regenerating axons (Milbreta et al, 2014). ChABC treatment affected morphology of laminin-positive blood vessel basement membranes and vessel-independent laminin deposits.…”
Section: Cspg Inhibition and Axon Regenerationmentioning
confidence: 99%
“…tPA deletion attenuated neurite outgrowth and sensory/motor functional recovery due to ChABC treatment and coadministration of ChABC and plasmin reversed the effects of tPA deficiency. ChABC treatment induced an extended period of astrocyte remodeling (up to 4 weeks) and a favored orientation of astrocytic processes directed toward injury area, which might become guidance bridges for regenerating axons (Milbreta et al, 2014). ChABC treatment affected morphology of laminin-positive blood vessel basement membranes and vessel-independent laminin deposits.…”
Section: Cspg Inhibition and Axon Regenerationmentioning
confidence: 99%
“…Orlando et al, however, showed that full digestion of motor cortex CSPG by ChABC aggravated motor deficits, suggesting that too much plasticity is not beneficial [246]. Milbreta et al found that ChABC altered astrocytic and vascular structure in injured spinal cords [226]. ChABC also promotes remyelination [185].…”
Section: Proteoglycansmentioning
confidence: 99%
“…In the intact spinal cord, NSCs are confined within the ependymal cell population and remain quiescent, and the expression of nestin is restricted . Our previous study shows that spinal cord NSCs are activated and proliferate robustly after SCI, using nestin immunofluorescence to represent NSCs .…”
Section: Resultsmentioning
confidence: 99%